Waqf-based social micro venture fund: a proposal for the Malay-muslim community in Singapore - Mohammad Hamber, Norliana; Mohamed Haneef, Mohamed Aslam (King Abdulaziz University Scientific Publishing Center, 2017)
The institution of waqf in Singapore is limited from playing a broader developmental role in society, especially with respect to the ethnic Malay community who consistently underperformed when measured against key socio-economic indicators. It maintains a largely religious orientation, as evidenced by the launch of Wakaf Ilmu for Islamic education in 2012. As a way of reinvigorating its developmental role to be in sync with the current needs of the Malay community in Singapore, this paper proposed the establishment of a waqf-based social micro venture fund (WSMVF) that promotes inclusive financial development for microentrepreneurs. This would help strengthen the community’s economic status, amidst existing efforts on education, social and religious fronts. It reduces vulnerabilities of low-income families, strengthens their earning capability and promotes upward social mobility. This paper looked at charitable institutions which practice innovative and progressive forms of giving that the WSMVF could adopt. Resultantly, WSMVF is conceptualized based on the content analysis of cash waqf operations, profit and loss sharing modes and venture capital strategies. The organizational structure and operations of WSMVF bring new features into the present institution of waqf in Singapore, effectively expanding its role in the community